Atypical Presentation of Unicuspid Unicommissural Aortic Valve in Infant - Islam, Md Tariqul; Hussain, Mohd Zahid; Karim, Tahmina; Bhuiyan, Md Mostafizur Rahman (Bangladesh Journal of Child Health, 2019)
Unicuspid aortic valve (UAV) is a very rare congenital heart defect with an ill-defined natural history. It’s very important to diagnose early as UAV has a risk of sudden cardiac death and association of other congenital anomalies. Here we present a case of unicommissural UAV with severe AS, severe LV dysfunction diagnosed by colour doppler TT echo, successfully treated with balloon valvoplasty (BAV). Bangladesh J Child Health 2019; VOL 43 (2) :117-121